2020
DOI: 10.1242/jeb.237669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on physiological performance and behavioral thermoregulation in an invasive fish, the round goby

Abstract: Invasive species exert negative impacts on biodiversity and ecosystems on a global scale, which may be enhanced in the future by climate change. Knowledge of how invasive species respond physiologically and behaviorally to novel and changing environments can improve our understanding of which traits enable the ecological success of these species, and potentially facilitate mitigation efforts. We examined the effects of acclimation to temperatures ranging from 5 to 28°C on aerobic metabolic rates, upper tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 114 publications
(163 reference statements)
1
45
0
Order By: Relevance
“…Acclimation can allow an organism to shift its thermal tolerance upward, but there are still physiological constraints that cannot be overcome, and prolonged exposure to high temperature can impose metabolic costs (Pörtner and Farrell 2008;Schulte 2014). Metabolic rates in multiple populations of round goby increase with temperature, particularly past 26°C (Lee and Johnson 2005;Drouillard et al 2018;Christensen et al 2021); therefore, at these elevated temperatures there are higher energetic demands placed on gobies, requiring physiological adjustment. In studies of brook trout (Salvelinus fontinalis), CTmax has been found to plateau between 20°C and 25°C, and molecular stress responses increase past 20°C (Chadwick and McCormick 2017;Morrison et al 2020).…”
Section: Critical Thermal Maximum and Acclimation Capacitymentioning
confidence: 99%
See 3 more Smart Citations
“…Acclimation can allow an organism to shift its thermal tolerance upward, but there are still physiological constraints that cannot be overcome, and prolonged exposure to high temperature can impose metabolic costs (Pörtner and Farrell 2008;Schulte 2014). Metabolic rates in multiple populations of round goby increase with temperature, particularly past 26°C (Lee and Johnson 2005;Drouillard et al 2018;Christensen et al 2021); therefore, at these elevated temperatures there are higher energetic demands placed on gobies, requiring physiological adjustment. In studies of brook trout (Salvelinus fontinalis), CTmax has been found to plateau between 20°C and 25°C, and molecular stress responses increase past 20°C (Chadwick and McCormick 2017;Morrison et al 2020).…”
Section: Critical Thermal Maximum and Acclimation Capacitymentioning
confidence: 99%
“…Overall, reduced feeding rates of round goby are likely due to performance trade-offs and behavioural changes associated with elevated temperatures. As described above, elevated metabolic rates have been measured at high temperatures (≥26°C) in round goby (Lee and Johnson 2005;Drouillard et al 2018;Christensen et al 2021). Acclimation to stressful temperatures introduces trade-offs between maintaining metabolic function and resource acquisition (Schulte 2015)-such that as an organism's metabolism is driven higher, more energy is required for simple performance maintenance (Morley et al 2019).…”
Section: Feeding Behaviour and Body Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…natural boulder reefs or man-made structures like harbor walls and jetties; Young et al 2010;Kornis et al 2012). Round gobies possess several invasive characteristics such as high competitiveness for territory, a broad diet, dispersal ability, and broad temperature and salinity tolerances (Kornis et al 2012;Azour et al 2015;Behrens et al 2017;Christensen et al 2021). As such, the round goby is generally thought to have negative impacts on recipient ecosystems and indigenous taxa.…”
Section: Article (Brief Communication Format)mentioning
confidence: 99%